The Cell-Surface Marker Sushi Containing Domain 2 Facilitates Establishment of Human Naive Pluripotent Stem Cells - Bredenkamp, Nicholas (Stem Cell Reports, 2019)
Recently naive human pluripotent stem cells (hPSCs) have been described that relate to an earlier stage of development than conventional hPSCs. Naive hPSCs remain challenging to generate and authenticate, however. Here we report that Sushi Containing Domain 2 (SUSD2) is a robust cell-surface marker of naive hPSCs in the embryo and in vitro. SUSD2 transcripts are enriched in the pre-implantation epiblast of human blastocysts and immunostaining shows localization of SUSD2 to KLF17-positive epiblast cells. SUSD2 mRNA is strongly expressed in naive hPSCs but is negligible in other hPSCs. SUSD2 immunostaining of live or fixed cells provides unambiguous discrimination of naive versus conventional hPSCs. SUSD2 staining or flow cytometry enable monitoring of naive hPSCs in maintenance culture, and their isolation and quantification during resetting of conventional hPSCs or somatic cell reprogramming. Thus SUSD2 is a powerful non-invasive tool for reliable identification and purification of the naive hPSC phenotype.